Digital technologies in architecture and engineering: Exploring an engaged interaction within curricula - Eloy, S.; Dias, J.; Lopes, P. F.; Vilar, E. (Handbook of research on applied e-learning in engineering and architecture education, 2016)
This chapter focuses on the development and adoption of new Multimedia, Computer Aided Design, and other ICT technologies for both Architecture and Computer Sciences curricula and highlights the multidisciplinary work that can be accomplished when these two areas work together. We describe in detail the addressed educational skills and the developed research and we highlight the contributions towards the improvements of teaching and learning in those areas. We discuss in detail the role of Digital technologies, such as Virtual Reality, Augmented Reality, Multimedia, 3D Modelling software systems, Design Processes and its evaluation tools, such as Shape Grammar and Space Syntax, within the Architecture curricula.